From Shadows to Spotlight: Analyzing Protodiplomatic Strategies in the 2022 Russia-Ukraine Crisis - Fathun, Laode Muhammad; Elyta, Elyta (Jurnal Keamanan Nasional, 2023)
This article aims to analyze the activities of protodiplomacy in the series of conflicts between Russia and Ukraine in 2022. This paper uses qualitative methodology with a case study method. Data collection techniques and, data sources use secondary data through ethnography. In addition, the data analysis technique used is a tracking process to review the historical traces of the occurrence of protodiplomacy in Ukraine. Based on the results of the author’s study, the results obtained are that protodiplomacy is a districtarea activity within the state in the form of a Union or Decentralization that seeks to secede from the territory of the country due to differences in various sides. Paradiplomacy activities as a foreign relations strategy carried out by sub-state actors or local governments are the beginning of protodiplomacy. This means that paradiplomacy activities have the potential to become protodiplomacy if there is no political control in the government’s political governance system. So that paradiplomacy can move as a global political agency to seek support and separate itself from the territory of the country. This research argues that the occurrence of protodiplomacy by Luhansk is due to differences in Culture, Political Justice, and Economic Justice. Protodiplomacy is also known as Identity Paradiplomacy because of the disintegration that occurs due to differences in identity so that regions act to secede. The pro-diplomacy activities that occurred in Luhansk, the Ukrainian region, were also not leas from the support and conflict that struck between Russia and Ukraine. The implication is that Luhansk is more free to choose and move. Moreover, Luhansk has the same historical traces as Russia. Thus, political support became an instrument for Luhansk to secede. Thus, the phenomenon of great power through invasion became a new tradition in the study of contemporary international relations. And it marks the return of great power in global conflicts. On the other hand, the security threat to Ukraine comes not only from the Russian state but from within the country, namely protodiplomacy (desecuritization).